METHOD OF TESTING PLASTIC PRODUCTS MANUFACTURED USING 3D PRINTING FOR STRENGTH IN BENDING (Collection of scientific works «Modern structures of metal and wood», 2024)
The  main  methods  of  mechanical  testing  of  composite  materials  include: determination of material strength under tension, bending, torsion, shock loads, compression, etc. This article presents the preparatory stage of conducting experimental studies on determining the bending  strength  of  structural  elements  made  of  ABS plastic,  manufactured  with  the  help  of  3D printing. As a result 2 series of experimental samples are indicated, which differ in the shape of the cross section (specimens of 1 st  series have rectangular section, samples of 2 nd  series have T-shaped section),  appropriate  dimensions  and  a  test  scheme  are  established  in  accordance  with  the requirements  of  regulatory  documents.  The  percentage  of  filling  of  the  internal  cavity  of  the experimental elements with polymer material was determined, namely 10%, 50% and 100%. The algorithm of preparation and direct execution of the planned tests under the action of a static short-term load is described. The predicted schemes and criteria for the destruction of the samples, as well as the conditions for stopping the tests, are given.